The effect of size, morphology and surface properties of mesoporous silica nanoparticles on pharmacokinetic aspects and potential toxicity concerns - Niroumand, Uranous; Firouzabadi, Negar; Goshtasbi, Ghazal; Hassani, Bahareh; Ghasemiyeh, Parisa; Mohammadi-Samani, Soliman (Frontiers in Materials, 2023)
Mesoporous silica nanoparticles (MSNs) are considered as suitable delivery vehicles considering their unique characteristics. Various physicochemical characteristics of MSNs govern their pharmacokinetic parameters which affect the disposition of these nanoparticles in the body. Along with the advantages of MSNs, the toxicity of nanoparticles entering the body is a major concern. Various factors such as particle size, surface charge, route of administration, etc. may affect organ toxicity of MSNs. The main target organs involved in the metabolism and elimination of MSNs are the kidney and the liver as well as the hematopoietic system. In this review, we first introduced the physicochemical characteristics of MSNs which affect the pharmacokinetic properties including drug absorption and bio-distribution. Thereafter, we discussed the mechanisms by which organ toxicity may occur. In this regard, the effects of various factors on organ-based MSNs toxicities and molecular mechanisms have been summarized. At last, we emphasized on the role of the physicochemical parameters on organ-based toxicities, and the proposed approaches to prevent or at least diminish MSN-related toxicities are discussed in detail.